Career maturity among students from three different types of school - Abdul Rahim, Nor Syazila; Mohd Noah, Sidek; Wan Jaafar, Wan Marzuki (Global Academic Excellence, 2018)
The purpose of this study is to identify the level of career maturity among students in three different types of schools which are SBPI Gombak (full boarding school), SMKA Maahad Hamidiah (religious school) and SMK Sri Serdang (daily school) in Lembah Klang, Selangor. This study is an ex-post facto research. The instrument used to examine career maturity is Career Maturity Inventory (CMI) introduced by Crites (1978) which was later translated by Tan Wat Jin (2005). A total of 182 students made up the study by using stratified sampling proportion and sample size calculated by G*Power software. Spearman’s Rho Correlation was used to analyse the relationship of the variables in this study while t test and one-way ANOVA was used to determine significant difference at .05 between the variables. The findings showed that there was no relation between socio-economic status and parents’ academic achievement to students’ career maturity level. In addition, it was found that there was no difference in attitude of career maturity among the schools, but there was a difference in competency of career maturity. The overall results showed that there was no difference in career maturity among the students from the three different types of schools.